Dental Pulp Dendritic Cells Migrate to Regional Lymph Nodes. (March 2014) - Bhingare, A.C.; Ohno, T.; Tomura, M.; Zhang, C.; Aramaki, O.; Otsuki, M.; Tagami, J.; Azuma, M.
Dendritic cell (DC) migration to regional lymph nodes (RLNs) is an essential step in adaptive immunity, and cell-surface antigens on migrating DCs greatly affect the quality and quantity of subsequent immune responses. Although MHC class II + DC-like cells exist in the dental pulp, the lineage and function of these cells remain unknown. Here, we identified migratory DCs from the dental pulp after cusp trimming and acid etching in KikGR mice, in which the photoconvertible fluorescent protein changed from green to red upon violet light exposure. Two major cell fractions from the dental pulp had migrated to the RLNs at 16 hrs after cusp treatment, which showed the following lineage markers in the main and second fractions: CD11c high CD11b ++ Ly6C low Ly6G low F4/80 + and CD11c med CD11b +++ Ly6C ++ Ly6G +++ F4/80 -, respectively. These lineage markers indicate that the former cells were DCs that had migrated through afferent lymphoid vessels, and the latter were granulocytes recruited via blood circulation. Migratory dental pulp DCs were mature, expressing the highest levels of CD273 (B7-DC) and CD86 co-stimulators and MHC class II. Our results suggest that cariogenic-bacteria-exposed dental pulp DCs migrate to RLNs and there trigger adaptive immune responses.